2020
DOI: 10.1590/1678-4499.20200262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different legume green manures on tropical soil microbiology after corn harvest

Abstract: Legume green manure is a popular practice for sustainable agriculture in tropical environments. The use of grain, forage and purely green manure legumes in a subhumid tropical area in Northeast Brazil was investigated to determine the total C and N contents and estimate C-microbial biomass, soil basal respiration, microbial and metabolic quotients, before and after green manures and after the following corn. It was hypothesized that, although all legumes would increase microbial biomass and activity, there wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Comparing the C-mic obtained in the present study with those obtained by Barros et al (2020) for legume green manure soils with the implementation of peanut, stylosanthes, and calopo after corn harvesting, we conclude that these same herbaceous used here had an increase of ~50, 30 and 25 kg ha -1 , respectively, in the rainy season, two years after the start of cultivation, revealing the effectiveness of these legumes in stimulating the soil microbial community the soil. On the other hand, our highest C-mic results are similar to that reported by Lira-Junior et al (2020a) in the dry season, and the legume row found silvopastoral system based on shrub-tree legume Gliricidia sepium and Mimosa caesalpinifolia, but ca.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Comparing the C-mic obtained in the present study with those obtained by Barros et al (2020) for legume green manure soils with the implementation of peanut, stylosanthes, and calopo after corn harvesting, we conclude that these same herbaceous used here had an increase of ~50, 30 and 25 kg ha -1 , respectively, in the rainy season, two years after the start of cultivation, revealing the effectiveness of these legumes in stimulating the soil microbial community the soil. On the other hand, our highest C-mic results are similar to that reported by Lira-Junior et al (2020a) in the dry season, and the legume row found silvopastoral system based on shrub-tree legume Gliricidia sepium and Mimosa caesalpinifolia, but ca.…”
Section: Discussionsupporting
confidence: 73%
“…Forage production from Arachis pintoi, Stylosanthes sp., and Calopogonium mucunoides has been reported (Boddey et al, 2020;Kumar et al, 2018) as their effects on structural soil protection and nutrient input equalizing from decomposing microbial activity (Vazquez et al, 2020). In addition, the use of herbaceous has been well established in studies with legume green manure (Barros et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In one evaluation of seven legumes green manure were able to maintain the total C and N contents in the soil after corn harvest. While forage legumes had higher metabolic stress than either grain or green manure ones, all the green manures presented lower stresses than either control treatment, indicating increased efficiency in organic matter decomposition (Barros et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…Among the different manures used, GLM performed well in improving the microbial population (Zhou et al, 2020). Because during the decomposition of fresh GLM, the activity of the microbes enhanced which in turn increased the microbial population (Barros et al, 2020). FYM also registered a significant result in the microbial population.…”
Section: Bacterial Populationmentioning
confidence: 97%